Comparison of propofol versus propofol-ketamine combination in pediatric oncologic procedures performed by non-anesthesiologists. - Chiaretti, Antonio; Ruggiero, Antonio; Barbi, Egidio; Pierri, Filomena; Maurizi, Palma; Fantacci, Claudia; Bersani, Giulia; Riccardi, Riccardo (Pediatr Blood Cancer, 2011)
BACKGROUND: Limited data are available on the best option (short acting sedatives, opioids, or ketamine) in oncologic procedural sedation performed by non-anesthesiologists. The aim of the present prospective study is to compare the safety and efficacy of propofol-ketamine versus propofol alone, managed by trained pediatricians, in children with cancer undergoing painful procedures. PROCEDURES: Data on 121 children with acute lymphatic leukemia (ALL) undergoing procedural sedations (lumbar punctures and bone marrow aspirations) were prospectively collected and included drug doses, side effects, pain assessment, and sedation degree. Children were randomly assigned to one of the two groups: P (n = 62) receiving propofol alone and K (n = 59) in whom a ketamine-propofol combination was used. RESULTS: In group K, the total dose of propofol required was significantly lower than in group P (3.9 ± 3.6 mg/kg vs. 5.1 ± 3.6 mg/kg; P < 0.001). The incidence of hypotension was also significantly lower (11% vs. 39%; P < 0.001). Major O(2) desaturations (defined as SatO(2) < 88%) occurred principally in group P (7 vs. 1; P = 0.05). Both best analgesia and shorter recovery time were obtained with the propofol-ketamine association. No differences were observed in the degree of sedation and in the awakening quality score between the two groups. CONCLUSIONS: The combination of propofol and ketamine produced statistically significant clinical advantages combined with a higher profile of safety in children with cancer undergoing painful procedures.
Keywords: Biopsy, Needle; Bone Marrow Examination; Child; Conscious Sedation; Female; Humans; Hypnotics and Sedatives; Ketamine; Male; Neoplasms; Pediatrics; Physicians; Propofol; Spinal Puncture